2011
DOI: 10.1164/rccm.201009-1535oc
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Exacerbations on Emphysema Progression in Chronic Obstructive Pulmonary Disease

Abstract: This is the first longitudinal study to demonstrate that exacerbations are involved in emphysema progression in patients with chronic obstructive pulmonary disease. Emphysema progression should be evaluated as part of the outcomes of exacerbations in the management of chronic obstructive pulmonary disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
198
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 161 publications
(209 citation statements)
references
References 46 publications
8
198
3
Order By: Relevance
“…Similarly, the mean frequency of hospital admission was 0.06, 0.10 and 0.09 for GOLD 2, GOLD 3 and GOLD 4, respectively, in the present study, whereas the mean was 0.11-0.2, 0.25-0.3 and 0.4-0.54 for GOLD 2, GOLD 3 and GOLD 4, respectively, in previous studies [1,4,10,12]. Such a lower frequency of exacerbation was also observed in the subgroup analysis of the Japanese patients participating the UPLIFT study and in another Japanese report [15,16]. The frequency of chronic bronchitis in our cohort was also lower compared to the other studies [12,17].…”
Section: Discussionsupporting
confidence: 80%
“…Similarly, the mean frequency of hospital admission was 0.06, 0.10 and 0.09 for GOLD 2, GOLD 3 and GOLD 4, respectively, in the present study, whereas the mean was 0.11-0.2, 0.25-0.3 and 0.4-0.54 for GOLD 2, GOLD 3 and GOLD 4, respectively, in previous studies [1,4,10,12]. Such a lower frequency of exacerbation was also observed in the subgroup analysis of the Japanese patients participating the UPLIFT study and in another Japanese report [15,16]. The frequency of chronic bronchitis in our cohort was also lower compared to the other studies [12,17].…”
Section: Discussionsupporting
confidence: 80%
“…Tanabe et al (38) reported that changes in the distribution of low-attenuation areas on computerized tomography images of COPD patients were consistent with the coalescence of neighboring low-attenuation areas due to alveolar wall destruction. Since tissue destruction is the primary mechanism that drives airspace enlargement, AECOPD should also contribute to the progression of COPD.…”
mentioning
confidence: 90%
“…[26] The clinical impact of exacerbations on various aspects of the disease has been demonstrated in numerous studies. [27] We know that exacerbations produce worsening symptoms, increase morbidity,[28,29] impair quality of life,[30] increase functional impairment,[31] relate to various comorbidities,[32,33] worsen clinical findings reported by patients,[34] and, ultimately, relate to the progression of disease [35] with a major impact on prognosis. [36] In addition, exacerbations have a significant impact on the financial burden of the disease for the health system.…”
Section: Discussionmentioning
confidence: 99%